Analysis of Children's Communication Education on the YouTube Series of Nussa and Rarra - Widya Dhea Aqtari; Nursapia Harahap (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
This study aims to figure out how the digitalization era is used by parents to provide education to their children both formal education in school and informal education outside school, as well as to find out how the media, especially the YouTube series Nussa and Rarra, could provide communication education that is packaged with Islamic nuances. Therefore, moral values are created in children and parents in everyday life. This research uses case study research method, which is research that focuses on a particular case to be observed and analyzed, as well as the need for deep analysis so that the results obtained will be accurate. Data collection techniques were carried out using interviews and observation as primary data and also documentation as secondary data. The results of the study show that it is true that YouTube is used as an alternative educational medium for children as long as it is under parents supervision. In fact, several episodes that Rarra: Adab Menasehati, Rarra : Maaf, dan Rarra: Teman Spesial Rarra, have chosen to serve as samples have had a pretty good impact on the communication that occurred between parents and children, with notable changes in behavior gradually.